Student workbook : proficiency in enterprise communication - Sarudin, Isarji; Mohd Noor, Zainab; Tunku Ahmad, Tunku Badariah; Zubairi, Ainol Madziah; Abdul Rahman, Abdul Hamid (Prestariang Systems Sdn Bhd, 2013)
This workbook was written as a reference guide for students interested in taking the Proficiency in Enterprise Communication (PEC) Test offered by Prestariang Systems Sdn Bhd. It explains four language components assessed in the test, namely Listening, Speaking, Language and Reading, and Writing.